2004
DOI: 10.1161/01.res.0000144805.11519.1e
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Connexin 43 Dephosphorylation During Hypoxia and Reoxygenation Is Linked to Cellular ATP Levels

Abstract: Abstract-Altered gap junction coupling of cardiac myocytes during ischemia may contribute to development of lethal arrhythmias. The phosphoprotein connexin 43 (Cx43) is the major constituent of gap junctions. Dephosphorylation of Cx43 and uncoupling of gap junctions occur during ischemia, but the significance of Cx43 phosphorylation in this setting is unknown. Here we show that Cx43 dephosphorylation in synchronously contracting myocytes during ischemia is reversible, independent of hypoxia, and closely associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
59
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(65 citation statements)
references
References 59 publications
5
59
1
Order By: Relevance
“…Interestingly, dephosphorylation of Cx43 during hypoxia has also been linked to decreased availability of ATP. 47 In any event, more detailed information about changes in Cx43 phosphorylation state at particular residues is needed to fully understand molecular mechanisms of Cx43 redistribution and electrical uncoupling during ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, dephosphorylation of Cx43 during hypoxia has also been linked to decreased availability of ATP. 47 In any event, more detailed information about changes in Cx43 phosphorylation state at particular residues is needed to fully understand molecular mechanisms of Cx43 redistribution and electrical uncoupling during ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Cx43 is a phosphoprotein, and the phosphorylation/dephosphorylation of Cx43 plays important roles in the regulation of protein turnover dynamics (trafficking, plaque assembly, internalization and degradation) as well as channels gating properties. 1,[11][12][13][14] In the hearts subjected to acute ischemia, [15][16][17] and in non-ischemic heart failure, 18 as well as in dilated cardiomyopathy, 19 dephosphorylation of Cx43 was shown to play an important role in its disorganization and electrical uncoupling of ventricular cells under the pathological conditions. It is well known that ventricular hypertrophy is associated with the activation or inhibition of various types of protein kinases and/or phosphatases.…”
mentioning
confidence: 99%
“…We hypothesize two possible explanations for the reasons as to why tCx43 and npCx43 expression patterns were similar in both the IHD and non-IHD group. The first is that Cx43 is reversibly dephosphorylated and is rephosphorylated during hypoxia and reoxygenation according to nonlethal fluctuations in cellular ATP [5], which could be seen in early stage IHD as well as in the non-IHD groups. The second is that non-IHD group in our study also had some degree of global hypoxia that was similar to that in the IHD groups during the perimortem period, resulting in the redistribution of Cx43 expression in the myocardium, thus mimicking changes in the IHD group.…”
Section: Discussionmentioning
confidence: 99%
“…In normal cardiac muscle, Cx43 is phosphorylated and localized to the intercalated discs. However, harmful stimuli such as ischemia, hypoxia, and hypothermia induce dephosphorylation and redistribution of Cx43 to the cytoplasm and/or lateral cell borders of cardiomyocytes [4,5]. Beardslee et al [4] reported that during ischemia, total Cx43 (tCx43) undergoes progressive dephosphorylation and concomitant accumulation of non-phosphorylated Cx43 (npCx43).…”
mentioning
confidence: 99%